Participation of Endothelin in the postnatal development of the rat kidney: Molecular mechanisms involved - Lucas Humberto Oronel; María del Carmen Ortiz; Analía Czerniczyniec; Rocío Marinoni; María Ángeles Magnanelli; Silvia Lores Arnaiz; María Florencia Albertoni Borghese; Mónica P. Majowicz (PLoS ONE, 2026)
Some adult diseases such as hypertension and kidney disease may have their origins in early life, due to exposure to different adverse stressors. Previously we demonstrated that the administration of a dual endothelin receptor antagonist (ERA) to Sprague-Dawley (SD) rats from day 1–21 of life decreased glomerular number, predisposing adult male rats to salt sensitivity. This new study explores some early molecular mechanisms underlying the alterations observed in the kidneys of ERA-treated rats during the postnatal period, evaluating sex differences. Newborn male and female SD rats were treated with a dual ERA from day 1–6 and then sacrificed on day 7 of life to obtain the kidneys for the preparation of homogenates and mitochondrial fractions to assess: renal cell proliferation and apoptosis, nitric oxide synthases (Nos), neuronal isoform (Nos1) and endothelial isoform (Nos3) mRNA expression, NADPH- diaphorase (NADPH-d) activity, oxidative stress markers and antioxidant enzymes. ERA-treated male rats showed increased thiobarbituric acid-reacting substances (TBARS) and decreased nitric oxide (NO) to superoxide anion (O 2 - ) ratio, with lower NADPH-d activity in the structures that give rise to glomeruli. Sex differences were observed in Nos1 and Nos3 mRNA expression, H 2 O 2 production, and catalase activity, being females more protected than males. The alterations observed in the kidneys of ERA-treated rats during the early postnatal period could be due to a renal imbalance between NO and ROS, with increased oxidative stress, and a misbalance between proliferation and apoptosis. Our current findings show some molecular mechanisms underlying Endothelin inhibition in the early postnatal period, with potential utility for designing reprogramming strategies.